Learning and using geographic information systems - Wilpen L. Gorr (Thomson Course Technology, 2007)
Due to the growing demand for Geographic Information Systems within the MIS, Public Policy, and Business School curriculums, An Introduction to Geographic Information Systems and Step-by-Step Tutorial for ArcExplorer, offers a comprehensive guide that will empower users to master this compelling technology. Using carefully organized lessons and step-by-step instructions, this text will introduce users to principles and resources on GIS as well as specific instructions on ArcExplorer, a leading GIS software package